Spatial Analysis of Pulmonary Tuberculosis Distribution in Bitung City: The Role of Altitude and Population Density - Frelly Valentino Kuhon; Ronald Imanuel Ottay; Cicilia Pali; Jeini Ester Nelwan; Oksfriani Jufri Sumampouw (Lembaga Pengembangan Kinerja Dosen, 2024)
Pulmonary Tuberculosis (Pulmonary TB) remains a serious global and national health problem, with Indonesia ranking second in the global TB case burden. Bitung City is the area with the second highest cases of Pulmonary TB in North Sulawesi Province, with a prevalence rate that tends to increase. Environmental factors such as population density and the physical condition of the house are suspected to play a role in the spread of the disease. Spatial analysis is needed to understand disease distribution patterns to support effective, region-based interventions. This study aims to describe the spatial distribution of Tuberculosis disease in Bitung City based on the altitude of the place and population density. This study uses a spatial analysis approach by mapping data on area height, population density, and the average number of pulmonary TB cases per year (2020-2023 period) in each sub-district in Bitung City. The data is analyzed descriptively by grouping each variable into specific categories and visualized in the form of a thematic map. The results of the study show that all sub-districts in Bitung City are included in the lowland category (0-200 meters above sea level), so that no significant variation was found in terms of the height of the place. A total of five sub-districts have a high population density, namely Aertembaga, Girian, Madidir, Maesa, and Matuari. This sub-district with a high population density also recorded the highest number of pulmonary TB cases, with Maesa as the sub-district with the highest cases (97.5 cases per year), followed by Girian, Aertembaga, Matuari, and Madidir. It was concluded that the distribution of pulmonary TB cases in Bitung City did not show variation based on the altitude of the place, but had a correlation with population density. Districts with high population density tend to be the areas with the highest burden of Pulmonary TB cases. These findings emphasize the importance of public health interventions focused on densely populated areas to control the transmission of pulmonary TB.